Left Parietal Functional Connectivity Mediates the Association Between COMT rs4633 and Verbal Intelligence in Healthy Adults - Xu, Qiang; Fu, Jilian; Liu, Feng; Qin, Wen; Liu, Bing; Jiang, Tianzi; Yu, Chunshui (Frontiers in Neuroscience, 2018)
In Chinese Han population, Catechol-O-methyltransferase gene (COMT) rs4633 is found to be associated with impaired cognitive process. We aimed to investigate the association between COMT rs4633 and verbal intelligence and the underlying neural mechanisms in Chinese Han healthy young adults. In 256 Chinese Han healthy young adults, we explored the modulatory effects of COMT rs4633 on verbal intelligence quotient (VIQ) and functional connectivity density (FCD) of the brain and the mediation effect of FCD on the association between COMT and VIQ. We further investigated the association between the expression patterns of dopamine receptor genes and the effect of COMT on FCD in the human brain. COMT rs4633 TT homozygotes exhibited lower VIQ than CC homozygotes and TC heterozygotes, higher long-range FCD (lrFCD) than CC homozygotes and TC heterozygotes in the left superior frontal gyrus. TT homozygotes and TC heterozygotes showed higher lrFCD than CC homozygotes in the left inferior parietal lobule. The lrFCD differences across genotypic subgroups were negatively associated with the expression of DRD2 and DRD3 genes. The left parietal lrFCD mediated the association between COMT rs4633 and VIQ. These findings provide a biological pathway that COMT rs4633 affects verbal intelligence via modulating the lrFCD of the left inferior parietal lobule.